Green electricity and biowastes via biogas to bulk‐chemicals and fuels: The next move toward a sustainable bioeconomy. Issue 3 (8th May 2015) - Zeng, An‐Ping; Kaltschmitt, Martin
Abstract : To deal with the global challenges of limited fossil resources, climate change, and environmental pollution bioeconomy has been identified globally as a strategic development goal. In this regard, many industrial countries and regions have set very ambiguous targets: e.g. within the EU 25–30% of all chemicals and other industrial products as well as 5–10% of transportation fuels should be bio‐based by 2030. These targets are hardly achievable and not sustainable with presently known bio‐production systems, mainly due to constrains in substrate availability, limited product yield, and high processing costs. Thus, new concepts are desperately needed. Against this background, an innovative and sustainable concept is presented and discussed here. The central idea of the concept is the conversion of organic wastes into a widely usable product—biogas (CO2 +CH4 )—which is then used as a clean and uniform substrate for the synthesis of bulk‐chemicals and/or fuels, especially by using green electricity from wind and solar. Such a concept (shortened as E&G 2 C) has the potential to overcome major limitations of known bioproduction systems. Biogas as a substrate of biosynthesis has many unique advantages, including sustainability, efficiency, and flexibility. The use of electricity for biosynthesis with biogas represents an ideal system for efficient bioelectrochemical conversion. Here, the rationale behind the concept is illustrated, its sustainability is underpinned with concrete data, and the realization of the concept is discussed by looking at the possible conversion routes and key issues to be solved. The markets and perspectives provided by the concept E&G 2 C are also briefly addressed. In conclusion, the concept E&G 2 C provides a unique and innovative path for the next move toward a real sustainable bioeconomy.